A super wear-resistant self-lubricating carbon nanopolymer and its preparation process

By introducing modified phenolic resin fibers and pretreated graphene into surface-modified graphene oxide composite materials, ultra-wear-resistant self-lubricating carbon nanopolymers are prepared, which solves the problem that existing materials are prone to wear after long-term friction. , achieving higher toughness, wear resistance and self-lubricity.

CN119119678BActive Publication Date: 2025-02-11ZIBO SOLEI IND EQUIP MAINTENANCE TECH CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411605743.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-12
Publication Date
2025-02-11
Estimated Expiration
2044-11-12

AI Technical Summary

Technical Problem

Existing surface-modified graphene oxide composite materials are still prone to wear after long friction, and wear cracks spread rapidly, reducing the service life of the material.

Method used

Ultra-wear-resistant self-lubricating carbon nanopolymers are prepared by melt blending, molding and curing processes such as modified phenolic resin fibers and pretreated graphene. Modified phenolic resin fibers increase the toughness and wear resistance of the material. The presence of the fibers shares friction loads and hinders crack propagation.

Benefits of technology

It significantly improves the toughness and wear resistance of the material, extends the service life, reduces the wear rate, and improves the self-lubricity of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present application relates to the technical field of nanocomposite materials, and specifically discloses a super wear-resistant self-lubricating carbon nanopolymer and its preparation process. A super wear-resistant self-lubricating carbon nanopolymer is made of the following raw materials in parts by weight: 35-50 parts of phenolic resin, 5-10 parts of bisphenol F resin, 0.2-1 parts of defoamer, 5-10 parts of modified phenolic resin fiber, 1-1.5 parts of pretreated graphene, 5-10 parts of polytetrafluoroethylene, 12-18 parts of nano-alumina, 6-10 parts of talcum powder, 0.5-3 parts of zirconium oxide, 0.2-1 parts of leveling agent, 1-5 parts of silicon carbide, 0.2-1 parts of antioxidant, 0.2-1 parts of ultraviolet absorber, and 25-35 parts of cardanol. The super wear-resistant self-lubricating carbon nanopolymer prepared in this application has the advantages of good toughness and good wear resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of nanocomposite materials, and more specifically, to a super wear-resistant self-lubricating carbon nanopolymer and a preparation process thereof. Background Art

[0002] Mechanical bearings are constantly subject to friction during operation. Over time, wear problems will occur on the surface of the mechanical bearings, which will in turn affect the service life and performance of the mechanical bearings.

[0003] Nanocomposites are new materials with excellent properties prepared by dispersing nanoscale fillers into matrices such as polymers, metals or ceramics. Among them, the polymer matrix has good processing properties. Adding nanoparticles to the polymer can prepare high-performance composite materials, namely polymer-based nanocomposites. This polymer-based nanocomposite with high wear resistance and self-lubricity can repair the worn parts of mechanical bearings, thereby increasing the service life of mechanical bearings.

[0004] The Chinese patent application document with publication number CN108676198A discloses a method for preparing surface-modified graphene oxide and its composite material. The present invention melt-blends the surface-modified graphene oxide with phenolic resin, adds fillers and mixes them evenly, then kneads them, molds them to prepare composite materials, and then solidifies them to obtain surface-modified graphene oxide composite materials. The surface-modified graphene oxide has good dispersion stability and uniformity in the polymer and strong thermal stability; the preparation method of the composite material is simple and efficient, does not require the addition of organic solvents, and the obtained composite material has good mechanical properties and low wear rate.

[0005] In the above-mentioned Chinese patent application documents, the surface-modified graphene oxide composite material prepared is brittle. After being rubbed for a long time, the surface is still prone to wear, and once wear cracks appear, they will expand rapidly, reducing the service life of the composite material. Summary of the invention

[0006] In order to further improve the toughness and wear resistance of super wear-resistant self-lubricating carbon nanopolymers, the present application provides a super wear-resistant self-lubricating carbon nanopolymer and a preparation process thereof.

[0007] In the first aspect, the present application provides a super wear-resistant self-lubricating carbon nanopolymer, which adopts the following technical solution:

[0008] A super wear-resistant self-lubricating carbon nanopolymer is prepared from the following raw materials in parts by weight: 35-50 parts of phenolic resin, 5-10 parts of bisphenol F resin, 0.2-1 parts of defoaming agent, 5-10 parts of modified phenolic resin fiber, 1-1.5 parts of pretreated graphene, 5-10 parts of polytetrafluoroethylene, 12-18 parts of nano-alumina, 6-10 parts of talc, 0.5-3 parts of zirconium oxide, 0.2-1 parts of leveling agent, 1-5 parts of silicon carbide, 0.2-1 parts of antioxidant, 0.2-1 parts of ultraviolet absorber, and 25-35 parts of cardanol;

[0009] The preparation method of the modified phenolic resin fiber comprises the following steps:

[0010] (1) Preparation of modified phenolic resin: Phenol and formaldehyde aqueous solution are mixed evenly, hydrochloric acid is added to adjust the pH, carboxymethyl konjac glucomannan is added and mixed evenly, ethylene-acrylic acid copolymer is added and mixed evenly, and distilled to obtain modified phenolic resin;

[0011] (2) placing the modified phenolic resin in a spinning machine barrel for melt spinning, soaking the fibers in a mixed solution of formaldehyde and hydrochloric acid, taking out the treated fibers, washing, drying, and crushing them to obtain modified phenolic resin fibers;

[0012] The preparation method of the pretreated graphene comprises the following steps: uniformly dispersing graphene, polyvinyl alcohol, polyvinyl pyrrolidone and deionized water by ultrasonication, and spray drying to obtain the pretreated graphene.

[0013] By adopting the above technical solution, the modified phenolic resin fiber has good toughness and strength; adding the modified phenolic resin fiber to the polymer can increase the wear resistance of the polymer. The fiber can share the load during the friction process and reduce the wear of the resin matrix in the polymer. At the same time, the presence of the fiber can hinder the expansion and formation of cracks during the wear process, making the polymer surface smoother and reducing the wear rate.

[0014] Preferably, in step (1), the preparation method of carboxymethyl konjac glucomannan comprises the following steps: uniformly mixing konjac glucomannan and ethanol, heating, adding chloroacetic acid and sodium hydroxide and mixing, adding oxalic acid to adjust the pH to neutral, drying under reduced pressure, crushing, and grinding to obtain carboxymethyl konjac glucomannan.

[0015] By adopting the above technical scheme, the reaction system enables konjac glucomannan to evenly undergo carboxymethylation reaction, making the performance of carboxymethyl konjac glucomannan more stable, and participating in the process of generating modified phenolic resin, so that the modified phenolic resin has a regular structure, enhanced stability, and better toughness and strength; and it works together with graphene to improve the self-lubricating property of the polymer.

[0016] Preferably, in step (1), the mass ratio of phenol, formaldehyde aqueous solution, carboxymethyl konjac glucomannan and ethylene-acrylic acid copolymer is (1.37-1.56):1:(0.16-0.19):(0.12-0.15).

[0017] By adopting the above technical scheme, the prepared modified phenolic resin has good strength and toughness. The structure of the modified phenolic resin still has good orderliness. When subjected to external force, it can quickly transfer stress. The appropriate amount of flexible chain added can consume stress and improve the wear resistance of the modified phenolic resin.

[0018] Preferably, in step (2), the spinning temperature is 85-95° C. and the winding speed is 93-130 m / min.

[0019] By adopting the above technical scheme, the modified phenolic resin has good fluidity during the spinning process, the internal structure of the obtained fiber is uniform, the defects are few, and the fiber has good toughness; in addition, the fiber has good structural compactness, which increases the bonding force between the modified phenolic resin molecules, so that the fiber has higher strength and enhanced wear resistance.

[0020] Preferably, the mass ratio of the graphene, polyvinyl alcohol, polyvinyl pyrrolidone and deionized water is (0.3-0.5):(1.5-2):1:(8-9.5).

[0021] By adopting the above technical scheme, graphene can be evenly dispersed in deionized water, which is more conducive to the film formation of polyvinyl alcohol and polyvinyl pyrrolidone on the graphene surface. At the same time, the film layer formed by polyvinyl alcohol and polyvinyl pyrrolidone on the graphene surface is more stable and tough, and is not easy to break when subjected to external force. The prepared pretreated graphene has a strong bonding force with the modified phenolic resin fiber, and its dispersibility in the resin matrix is ​​improved, which can effectively absorb and disperse stress and improve the strength and toughness of the polymer.

[0022] Preferably, the mass ratio of the konjac glucomannan, chloroacetic acid and sodium hydroxide is 1:(0.5-0.8):(0.85-1.2).

[0023] By adopting the above technical scheme, the carboxymethylation degree of konjac glucomannan is improved, and the prepared modified phenolic resin fiber has better flexibility and plasticity, can better absorb energy when subjected to external force, undergoes elastic deformation instead of brittle fracture, and has better toughness.

[0024] Preferably, the leveling agent is one of a fluorocarbon leveling agent and a modified polyurethane leveling agent.

[0025] By adopting the above technical solution, after the fluorocarbon leveling agent forms a uniform film layer on the polymer surface, the friction coefficient of the polymer surface is reduced, thereby improving the self-lubricating property of the polymer; the molecular chain of the modified polyurethane is soft and has a certain elasticity, which increases the flexibility of the polymer and thus improves its toughness.

[0026] In a second aspect, the present application provides a process for preparing a super wear-resistant self-lubricating carbon nanopolymer, comprising the following steps:

[0027] S1: Phenolic resin and bisphenol F resin are mixed, heated, and stirred for 10-15 minutes;

[0028] S2: Add defoamer and stir the modified phenolic resin fiber for 10-15 minutes;

[0029] S3: Add pretreated graphene and stir for 10-15 minutes;

[0030] S4: Add polytetrafluoroethylene, nano-alumina, talcum powder, zirconium oxide, leveling agent, silicon carbide, antioxidant and ultraviolet absorber, and stir for 40-60 minutes;

[0031] S5: Cooling down, adding cardanol, mixing and stirring evenly to obtain a super wear-resistant self-lubricating carbon nanopolymer.

[0032] Preferably, the mixing temperature in step S1 is 75-90°C.

[0033] By adopting the above technical solution, the resin matrix has good fluidity and processability, which is conducive to the pretreatment of graphene, and the solid particles such as nano-alumina and talcum powder are evenly dispersed in the resin matrix, increasing the strength of the polymer. At the same time, it can quickly disperse and consume stress and improve the strength and toughness of the polymer.

[0034] Preferably, in step S5, the temperature after cooling is less than 60°C.

[0035] By adopting the above technical solution, the internal uniformity of the polymer is improved, and at the same time the polymer has good stability and processability.

[0036] In summary, this application has the following beneficial effects:

[0037] 1. Ethylene acrylic acid copolymer has good toughness and wear resistance. Its addition enhances the toughness of phenolic resin fiber. Phenolic resin fiber has good compatibility with phenolic resin and strong interface bonding force. The addition of fiber can quickly disperse the local stress of phenolic resin, and it is not easy to crack when subjected to stress for a long time, which increases the wear resistance of phenolic resin and thus improves the wear resistance of polymer.

[0038] 2. The hydroxyl group in polyvinyl alcohol and the carboxyl group in ethylene acrylic acid can undergo esterification reaction to enhance the bonding force between graphene and fiber. Since the fiber has good dispersibility in the resin matrix, the dispersibility of graphene is improved, and the interfacial bonding force between graphene and the resin matrix is ​​enhanced, thereby improving the wear resistance of the polymer.

[0039] 3. Carboxymethyl konjac glucomannan participates in the generation and curing process of phenolic resin to form a flexible network structure. The reaction activity of carboxymethylated konjac glucomannan in the generation and curing process of phenolic resin is reduced, the cross-linking density during curing is reduced, and the space for molecular chain movement in the network structure formed after curing is increased, which increases the toughness of phenolic resin and thus improves the toughness of the polymer. DETAILED DESCRIPTION

[0040] The present application is further described in detail below with reference to the embodiments.

[0041] Unless otherwise specified, the raw materials used in the examples and comparative examples of the present application are all commercially available.

[0042] Example 1

[0043] The ultra-wear-resistant self-lubricating carbon nanopolymer of this embodiment is made of the following raw materials: 35g of phenolic resin, 5g of bisphenol F resin, 0.2g of BYK-011 defoamer, 5g of modified phenolic resin fiber, 1g of pretreated graphene, 5g of polytetrafluoroethylene, 12g of nano-alumina, 6g of talcum powder, 0.5g of zirconium oxide, 0.2g of 375S leveling agent, 1g of silicon carbide, 0.2g of antioxidant 1010, 0.2g of 531 ultraviolet absorber, and 25g of cardanol.

[0044] The modified phenolic resin fiber preparation method of the present embodiment is as follows:

[0045] (1) Preparation of modified phenolic resin: 137 g of phenol and 100 g of a 37% formaldehyde aqueous solution were stirred at 80°C for 30 min, hydrochloric acid was added to adjust the pH to 4, 16 g of carboxymethyl konjac glucomannan was added, the reaction was continued for 2 h, 12 g of ethylene-acrylic acid copolymer was added, the mixture was stirred for 1 h, and vacuum distillation was performed for 30 min to obtain modified phenolic resin;

[0046] (2) The modified phenolic resin is placed in a spinning machine barrel and heated to 85°C for melt spinning. The spinneret hole diameter is 0.17 mm, the extrusion rate is 4 m / min, and the winding speed is 93 m / min. The obtained fiber is immersed in a mixed solution consisting of 100 g of a 25.5% formaldehyde aqueous solution and 100 g of a 20% hydrochloric acid solution, heated to 60°C, immersed for 6 h, taken out, washed, dried, and then the fiber is crushed into a state with an average length of 3 mm to obtain a modified phenolic resin fiber.

[0047] The preparation method of the carboxymethyl konjac glucomannan of the present embodiment is as follows:

[0048] 10 g of konjac glucomannan and 65 g of ethanol were mixed evenly, the temperature was raised to 50°C, 5 g of chloroacetic acid and 8.5 g of sodium hydroxide were added and mixed evenly, the mixture was reacted for 3 h, oxalic acid was added to adjust the pH to neutral, the mixture was dried under reduced pressure, crushed and ground to obtain carboxymethyl konjac glucomannan.

[0049] The preparation method of the pretreated graphene of this embodiment is as follows: 3 g of graphene, 15 g of polyvinyl alcohol, 10 g of polyvinyl pyrrolidone and 80 g of deionized water are uniformly dispersed by ultrasonication, and spray-dried at 80° C. to obtain the pretreated graphene.

[0050] The preparation process of the super wear-resistant self-lubricating carbon nanopolymer of this embodiment is as follows:

[0051] S1: Mix 35g of phenolic resin and 5g of bisphenol F resin, heat to 75°C, and stir for 10min;

[0052] S2: Add 0.2g BYK-011 defoamer and 5g modified phenolic resin fiber and stir for 10min;

[0053] S3: Add 1 g of pretreated graphene and stir for 10 min;

[0054] S4: Add 5g polytetrafluoroethylene, 12g nano-alumina, 6g talc, 0.5g zirconium oxide, 0.2g 375S leveling agent, 1g silicon carbide, 0.2g antioxidant 1010 and 0.2g 531 ultraviolet absorber, and stir for 40min;

[0055] S5: Cool down to 50°C, add 25g of cardanol and mix evenly to obtain a super wear-resistant self-lubricating carbon nanopolymer.

[0056] Example 2

[0057] The ultra-wear-resistant self-lubricating carbon nanopolymer of this embodiment is made of the following raw materials: 50g of phenolic resin, 10g of bisphenol F resin, 1g of BYK-011 defoamer, 10g of modified phenolic resin fiber, 1.5g of pretreated graphene, 10g of polytetrafluoroethylene, 18g of nano-alumina, 10g of talc, 3g of zirconium oxide, 1g of AKN-1377 leveling agent, 5g of silicon carbide, 1g of antioxidant 1076, 1g of 531 ultraviolet absorber, and 35g of cardanol.

[0058] The modified phenolic resin fiber preparation method of the present embodiment is as follows:

[0059] (1) Preparation of modified phenolic resin: 156 g of phenol and 100 g of a 37% formaldehyde aqueous solution were stirred at 80°C for 30 min, hydrochloric acid was added to adjust the pH to 4.5, 19 g of carboxymethyl konjac glucomannan was added, the reaction was continued for 2 h, 15 g of ethylene-acrylic acid copolymer was added, the mixture was stirred for 1 h, and the mixture was distilled under reduced pressure for 35 min to obtain a modified phenolic resin;

[0060] (2) The modified phenolic resin is placed in a spinning machine barrel and heated to 95°C for melt spinning, with a spinneret hole diameter of 0.17 mm, an extrusion rate of 4 m / min, and a winding speed of 130 m / min; the obtained fiber is immersed in a mixed solution consisting of 100 g of a 25.5% formaldehyde aqueous solution and 100 g of a 20% hydrochloric acid solution, heated to 60°C, immersed for 5 h, taken out, washed, dried, and then the fiber is crushed into a state with an average length of 2 mm to obtain a modified phenolic resin fiber.

[0061] The preparation method of the carboxymethyl konjac glucomannan of the present embodiment is as follows: 10g of konjac glucomannan and 65g of ethanol are mixed uniformly, the temperature is raised to 60°C, 8g of chloroacetic acid and 12g of sodium hydroxide are added and mixed uniformly, the reaction is carried out for 3h, oxalic acid is added to adjust the pH to neutral, the mixture is dried under reduced pressure, crushed, and ground to obtain carboxymethyl konjac glucomannan.

[0062] The preparation method of the pretreated graphene of this embodiment is as follows: 5 g of graphene, 20 g of polyvinyl alcohol, 10 g of polyvinyl pyrrolidone and 95 g of deionized water are uniformly dispersed by ultrasonication, and spray-dried at 90° C. to obtain the pretreated graphene.

[0063] The preparation process of the super wear-resistant self-lubricating carbon nanopolymer of this embodiment is as follows:

[0064] S1: Mix 50g of phenolic resin and 10g of bisphenol F resin, heat to 90°C, and stir for 15min;

[0065] S2: Add 1g BYK-011 defoamer and 10g modified phenolic resin fiber and stir for 15min;

[0066] S3: Add 1.5 g of pretreated graphene and stir for 15 min;

[0067] S4: Add 10g polytetrafluoroethylene, 18g nano-alumina, 10g talc, 3g zirconium oxide, 1g AKN-1377 leveling agent, 5g silicon carbide, 1g antioxidant 1076 and 1g 531 ultraviolet absorber, and stir for 60min;

[0068] S5: Cool down to 55° C., add 35 g of cardanol and mix evenly to obtain a super wear-resistant self-lubricating carbon nanopolymer.

[0069] Example 3

[0070] The ultra-wear-resistant self-lubricating carbon nanopolymer of this embodiment is made of the following raw materials: 45g of phenolic resin, 6g of bisphenol F resin, 0.5g of BYK-011 defoamer, 8g of modified phenolic resin fiber, 1.2g of pretreated graphene, 8g of polytetrafluoroethylene, 17g of nano-alumina, 9g of talcum powder, 1g of zirconium oxide, 0.5g of cx-313 leveling agent, 2g of silicon carbide, 0.5g of antioxidant 1098, 0.4g of 531 ultraviolet absorber, and 30g of cardanol.

[0071] The modified phenolic resin fiber preparation method of the present embodiment is as follows:

[0072] (1) Preparation of modified phenolic resin: 140 g of phenol and 100 g of a 37% formaldehyde aqueous solution were stirred at 80°C for 30 min, hydrochloric acid was added to adjust the pH to 5, 17 g of carboxymethyl konjac glucomannan was added, the reaction was continued for 2 h, 14 g of ethylene-acrylic acid copolymer was added, the mixture was stirred for 1 h, and the mixture was distilled under reduced pressure for 30 min to obtain a modified phenolic resin;

[0073] (2) The modified phenolic resin is placed in a spinning machine barrel and heated to 87°C for melt spinning. The spinneret hole diameter is 0.17 mm, the extrusion rate is 4 m / min, and the winding speed is 120 m / min. The obtained fiber is immersed in a mixed solution consisting of 100 g of a 25.5% formaldehyde aqueous solution and 100 g of a 20% hydrochloric acid solution, heated to 60°C, immersed for 5.5 h, taken out, washed, dried, and then the fiber is crushed into a state with an average length of 3 mm to obtain a modified phenolic resin fiber.

[0074] The preparation method of the carboxymethyl konjac glucomannan of the present embodiment is as follows: 10g of konjac glucomannan and 65g of ethanol are mixed uniformly, the temperature is raised to 55°C, 6g of chloroacetic acid and 9g of sodium hydroxide are added and mixed uniformly, the reaction is carried out for 3h, oxalic acid is added to adjust the pH to neutral, the mixture is dried under reduced pressure, crushed, and ground to obtain carboxymethyl konjac glucomannan.

[0075] The preparation method of the pretreated graphene of this embodiment is as follows: 3.5 g of graphene, 19 g of polyvinyl alcohol, 10 g of polyvinyl pyrrolidone and 90 g of deionized water are uniformly dispersed by ultrasonication, and spray-dried at 85° C. to obtain the pretreated graphene.

[0076] The preparation process of the super wear-resistant self-lubricating carbon nanopolymer of this embodiment is as follows:

[0077] S1: Mix 45g of phenolic resin and 6g of bisphenol F resin, heat to 85°C, and stir for 13min;

[0078] S2: Add 0.5g BYK-011 defoamer and 8g modified phenolic resin fiber and stir for 13min;

[0079] S3: Add 1.2 g of pretreated graphene and stir for 13 min;

[0080] S4: Add 8g polytetrafluoroethylene, 17g nano-alumina, 9g talc, 1g zirconium oxide, 0.5g cx-313 leveling agent, 2g silicon carbide, 0.5g antioxidant 1098 and 0.4g 531 ultraviolet absorber, and stir for 55min;

[0081] S5: Cool down to 56° C., add 30 g of cardanol and mix evenly to obtain a super wear-resistant self-lubricating carbon nanopolymer.

[0082] Comparative Example 1

[0083] The ultra-wear-resistant self-lubricating carbon nanopolymer of this comparative example is made of the following raw materials: 35g of phenolic resin, 5g of bisphenol F resin, 0.2g of BYK-011 defoamer, 1g of pretreated graphene, 5g of polytetrafluoroethylene, 12g of nano-alumina, 6g of talcum powder, 0.5g of zirconium oxide, 0.2g of 375S leveling agent, 1g of silicon carbide, 0.2g of antioxidant 1010, 0.2g of 531 ultraviolet absorber, and 25g of cardanol.

[0084] The preparation method of the phenolic resin fiber of this comparative example is as follows:

[0085] (1) Preparation of phenolic resin: 137 g of phenol and 100 g of 37% formaldehyde aqueous solution were stirred at 80°C for 30 min, hydrochloric acid was added to adjust the pH to 4, the reaction was continued with stirring for 3 h, and the phenolic resin was obtained by vacuum distillation for 30 min.

[0086] (2) placing phenolic resin in a spinning machine barrel and heating it to 85°C for melt spinning, with a spinneret hole diameter of 0.17 mm, an extrusion rate of 4 m / min, and a winding speed of 93 m / min; soaking the obtained fiber in a mixed solution consisting of 100 g of a 25.5% by mass formaldehyde aqueous solution and 100 g of a 20% by mass hydrochloric acid, heating it to 60°C, soaking it for 6 h, taking it out, washing it, drying it, and then crushing the fiber into a state with an average length of 3 mm to obtain phenolic resin fiber.

[0087] The preparation method of the pretreated graphene of this comparative example is as follows: 3 g of graphene, 15 g of polyvinyl alcohol, 10 g of polyvinyl pyrrolidone and 80 g of deionized water are uniformly dispersed by ultrasonication, and spray-dried at 80° C. to obtain the pretreated graphene.

[0088] The preparation process of the ultra-wear-resistant self-lubricating carbon nanopolymer of this comparative example is as follows:

[0089] S1: Mix 35g of phenolic resin and 5g of bisphenol F resin, heat to 75°C, and stir for 10min;

[0090] S2: Add 0.2 g BYK-011 defoamer and 1 g pretreated graphene and stir for 10 min;

[0091] S3: Add 5g polytetrafluoroethylene, 12g nano-alumina, 6g talc, 0.5g zirconium oxide, 0.2g 375S leveling agent, 1g silicon carbide, 0.2g antioxidant 1010 and 0.2g 531 UV absorber, and stir for 40min;

[0092] S5: Cool down to 50° C., add 25 g of cardanol and mix evenly to obtain a super wear-resistant self-lubricating carbon nanopolymer.

[0093] Comparative Example 2

[0094] The ultra-wear-resistant self-lubricating carbon nanopolymer of this comparative example is made of the following raw materials: 35g of phenolic resin, 5g of bisphenol F resin, 0.2g of BYK-011 defoamer, 5g of modified phenolic resin fiber, 1g of pretreated graphene, 5g of polytetrafluoroethylene, 12g of nano-alumina, 6g of talcum powder, 0.5g of zirconium oxide, 0.2g of 375S leveling agent, 1g of silicon carbide, 0.2g of antioxidant 1010, 0.2g of 531 ultraviolet absorber, and 25g of cardanol.

[0095] The preparation method of the modified phenolic resin fiber of this comparative example is as follows:

[0096] (1) Preparation of modified phenolic resin: 137 g of phenol and 100 g of a 37% formaldehyde aqueous solution were stirred at 80°C for 30 min, hydrochloric acid was added to adjust the pH to 4, 16 g of carboxymethyl konjac glucomannan was added, the reaction was continued for 2 h, 12 g of ethylene-acrylic acid copolymer was added, the mixture was stirred for 1 h, and the mixture was distilled under reduced pressure for 30 min to obtain a modified phenolic resin;

[0097] (2) The modified phenolic resin is placed in a spinning machine barrel and heated to 85°C for melt spinning. The spinneret hole diameter is 0.17 mm, the extrusion rate is 4 m / min, and the winding speed is 93 m / min. The obtained fiber is immersed in a mixed solution consisting of 100 g of a 25.5% formaldehyde aqueous solution and 100 g of a 20% hydrochloric acid solution, heated to 60°C, immersed for 6 h, taken out, washed, dried, and then the fiber is crushed into a state with an average length of 3 mm to obtain a modified phenolic resin fiber.

[0098] The preparation method of the carboxymethyl konjac glucomannan of this comparative example is as follows:

[0099] 10 g of konjac glucomannan and 65 g of ethanol were mixed evenly, the temperature was raised to 50°C, 5 g of chloroacetic acid and 8.5 g of sodium hydroxide were added and mixed evenly, the mixture was reacted for 3 h, oxalic acid was added to adjust the pH to neutral, the mixture was dried under reduced pressure, crushed and ground to obtain carboxymethyl konjac glucomannan.

[0100] The preparation method of the pretreated graphene of this comparative example is as follows: 3 g of graphene, 10 g of polyvinyl pyrrolidone and 80 g of deionized water are uniformly dispersed by ultrasonic dispersion, and spray-dried at 80° C. to obtain the pretreated graphene.

[0101] The preparation process of the ultra-wear-resistant self-lubricating carbon nanopolymer of this comparative example is as follows:

[0102] S1: Mix 35g of phenolic resin and 5g of bisphenol F resin, heat to 75°C, and stir for 10min;

[0103] S2: Add 0.2g BYK-011 defoamer and 5g modified phenolic resin fiber and stir for 10min;

[0104] S3: Add 1 g of pretreated graphene and stir for 10 min;

[0105] S4: Add 5g polytetrafluoroethylene, 12g nano-alumina, 6g talc, 0.5g zirconium oxide, 0.2g 375S leveling agent, 1g silicon carbide, 0.2g antioxidant 1010 and 0.2g 531 ultraviolet absorber, and stir for 40min;

[0106] S5: Cool down to 50° C., add 25 g of cardanol and mix evenly to obtain a super wear-resistant self-lubricating carbon nanopolymer.

[0107] Performance testing

[0108] The preparation method of the super wear-resistant self-lubricating carbon nanopolymer test sample is as follows: the super wear-resistant self-lubricating carbon nanopolymer is placed in a mold, a pressure of 30 MPa is applied, the temperature is increased to 140° C., and hot pressing is performed for 12 hours to obtain the super wear-resistant self-lubricating carbon nanopolymer test sample.

[0109] The performance testing method of super wear-resistant self-lubricating carbon nanopolymer is as follows:

[0110] 1. Friction test

[0111] The friction test of super wear-resistant self-lubricating carbon nanopolymer refers to the national standard GB / T3960-2016, the sample size is 30mm×7mm×6mm, and the load is 196N.

[0112] 2. Tensile performance test

[0113] The tensile property test of super wear-resistant self-lubricating carbon nanopolymer refers to the national standard GB / T1040-2006, the sample size is 75mm×5mm×2mm, and the test rate is 2mm / min.

[0114] 3. Bending performance test

[0115] The bending performance test method of super wear-resistant self-lubricating carbon nanopolymer refers to the national standard GB / T9341-2008, the sample length is 80mm, the sample width is 10mm, the sample thickness is 4mm, and the test speed is 2mm / min.

[0116] The performance test data of Example 1, Example 2, Example 3, Comparative Example 1 and Comparative Example 2 are shown in Table 1 below:

[0117] Table 1 Test data

[0118]

[0119] It can be seen from the analysis of Examples 1-3 and Comparative Examples 1-2 in combination with Table 1 that the addition of modified phenolic resin fibers and pretreated graphene to the ultra-wear-resistant self-lubricating carbon nanopolymer can improve its toughness and wear resistance.

[0120] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A super wear-resistant self-lubricating carbon nanopolymer, characterized in that: The invention is prepared from the following raw materials in parts by weight: 35-50 parts of phenolic resin, 5-10 parts of bisphenol F resin, 0.2-1 parts of defoaming agent, 5-10 parts of modified phenolic resin fiber, 1-1.5 parts of pretreated graphene, 5-10 parts of polytetrafluoroethylene, 12-18 parts of nano-alumina, 6-10 parts of talc, 0.5-3 parts of zirconium oxide, 0.2-1 parts of leveling agent, 1-5 parts of silicon carbide, 0.2-1 parts of antioxidant, 0.2-1 parts of ultraviolet absorber and 25-35 parts of cardanol. The preparation method of the modified phenolic resin fiber comprises the following steps: (1) Preparation of modified phenolic resin: Phenol and formaldehyde aqueous solution are mixed evenly, hydrochloric acid is added to adjust the pH, carboxymethyl konjac glucomannan is added and mixed evenly, ethylene-acrylic acid copolymer is added and mixed evenly, and distilled to obtain modified phenolic resin; (2) placing the modified phenolic resin in a spinning machine barrel for melt spinning, soaking the fibers in a mixed solution of formaldehyde and hydrochloric acid, taking out the treated fibers, washing, drying, and crushing them to obtain modified phenolic resin fibers; The preparation method of the pretreated graphene comprises the following steps: uniformly dispersing graphene, polyvinyl alcohol, polyvinyl pyrrolidone and deionized water by ultrasonication, and spray drying to obtain the pretreated graphene; The mass ratio of the graphene, polyvinyl alcohol, polyvinyl pyrrolidone and deionized water is (0.3-0.5):(1.5-2):1:(8-9.5); In the step (1), the mass ratio of phenol, formaldehyde aqueous solution, carboxymethyl konjac glucomannan and ethylene-acrylic acid copolymer is (1.37-1.56):1:(0.16-0.19):(0.12-0.15).

2. The super wear-resistant self-lubricating carbon nanopolymer according to claim 1, characterized in that: In the step (1), the preparation method of carboxymethyl konjac glucomannan comprises the following steps: mixing konjac glucomannan and ethanol evenly, heating, adding chloroacetic acid and sodium hydroxide and mixing evenly, adding oxalic acid to adjust the pH to neutral, drying under reduced pressure, crushing, and grinding to obtain carboxymethyl konjac glucomannan.

3. The super wear-resistant self-lubricating carbon nanopolymer according to claim 1, characterized in that: In the step (2), the spinning temperature is 85-95° C. and the winding speed is 93-130 m / min.

4. The super wear-resistant self-lubricating carbon nanopolymer according to claim 2, characterized in that: The mass ratio of the konjac glucomannan, chloroacetic acid and sodium hydroxide is 1:(0.5-0.8):(0.85-1.2).

5. The super wear-resistant self-lubricating carbon nanopolymer according to claim 1, characterized in that: The leveling agent is one of a fluorocarbon leveling agent and a modified polyurethane leveling agent.

6. A process for preparing the ultra-wear-resistant self-lubricating carbon nanopolymer as claimed in claim 1, comprising the following steps: S1: Phenolic resin and bisphenol F resin are mixed, heated, and stirred for 10-15 minutes; S2: Add defoamer and modified phenolic resin fiber and stir for 10-15 minutes; S3: Add pretreated graphene and stir for 10-15 minutes; S4: Add polytetrafluoroethylene, nano-alumina, talcum powder, zirconium oxide, leveling agent, silicon carbide, antioxidant and ultraviolet absorber, and stir for 40-60 minutes; S5: Cooling down, adding cardanol, mixing and stirring evenly to obtain a super wear-resistant self-lubricating carbon nanopolymer.

7. The process for preparing a super wear-resistant self-lubricating carbon nanopolymer according to claim 6, characterized in that: The mixing temperature in step S1 is 75-90°C.

8. The process for preparing a super wear-resistant self-lubricating carbon nanopolymer according to claim 6, characterized in that: In step S5, the temperature after cooling is less than 60°C.

Citation Information

Patent Citations

  • Preparation methods of surface-modified graphene oxide and surface-modified graphene oxide composite material

    CN108676198A

  • Modified phenolic resin fiber, and preparation method and application thereof

    CN106811822A

  • Glass fiber reinforced plastic and preparation method thereof

    CN118165440A